given the system of equations:
![\begin{gathered} x+4y=9\rightarrow(1) \\ y-2z=-1\rightarrow(2) \\ -4x-7y+6z=-21\rightarrow(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1ym2vf2p1kyy5sgvtw4v39hn97ism57l0g.png)
We will solve the system by substitution as follows:
From equation (2)
![y=2z-1\rightarrow(4)](https://img.qammunity.org/2023/formulas/mathematics/college/i9k2wl3zdb3kmlyrba3r88k9r88ax5uth6.png)
substitute with (y) from equation (4) into equation (1)
![\begin{gathered} x+4(2z-1)=9 \\ x+8z-4=9 \\ x=13-8z\rightarrow(5) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3pyif3yhfavsotmmhrdubxb48subg7qtue.png)
From the equation (4) and (5) substitute with (x) and (y) into equation (3):
![-4(13-8z)-7(2z-1)+6z=-21](https://img.qammunity.org/2023/formulas/mathematics/college/8ffk2rc8r2xtawx6u1wd9jnj2twe1s6hzo.png)
solve the equation to find the value of (z):
![\begin{gathered} -52+32z-14z+7+6z=-21 \\ 24z=-21+52-7 \\ 24z=24 \\ z=(24)/(24)=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5hvk9fjmub1rwauffylqygh853k97suw8z.png)
substitute into the equations (4) and (5) to find the values of (x, y)
![\begin{gathered} x=13-8z=13-8\cdot1=5 \\ y=2z-1=2\cdot1-1=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/sey7brnf5eszr6m6h2yfur8h8w1mk6xh7v.png)
So, the answer will be:
The system has only one solution
x = 5
y = 1
z = 1